Coiling of ruptured, wide-necked basilar tip aneurysm using double Comaneci technique. (18th May 2018) - Sirakov, Stanimir S; Sirakov, Alexander; Hristov, Hristo; Raychev, Radoslav
Abstract : In this report, we present a novel technique of successful coil embolisation using temporary deployment of two Comaneci devices placed in Y configuration across a wide-neck ruptured basilar tip aneurysm. The placement of two devices across the wide aneurysm neck allowed optimal coverage for safe coil delivery, while maintaining parent vessel patency. This case highlights the unique and safe applicability of two crossed Comaneci devices in a ruptured aneurysm with unfavourable anatomy, ultimately resulting in complete aneurysm obliteration. To our knowledge, this is the first reported case of double Comaneci usage in a wide-neck ruptured aneurysm. This technique can be potentially applied in challenging wide-neck bifurcation aneurysms, particularly when double antiplatelet therapy is of concern.